NILAI KEWAJIBAN TERHADAP DIRI SENDIRI DALAM NOVEL TAK SEMPURNA KARYA FAHD DJIBRAN FEAT BONDAN PRAKOSO DAN FADE2BLACK - Kristin Dwi Wulandari (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
This research was conductedin order to determinethe obligationsof selfin the novel Imperfect. Source of research datais sourced from the novel Imper fectworks Fahd Djibran, Bondan Prakoso feat Fade2Black. Data collection techniques used in this researchis the technique of reading and recording. The data analysis technique used in this research iscontent analysis techniques. The instrumentof this study are researchers. The results showed that the obligation to selfin the novel Imperfect be grateful, be highly motivated, learning, faith, regrets